Weight Loss in Older Persons: New Therapeutic Approaches - Morley, John E. (Current Pharmaceutical Design, 2007)
There is now a large body of evidence that weight loss in older persons not only increases mortality, but also increases the incidence of hip fracture, functional deterioration and institutionalization. Weight loss is a central component of frailty. There is evidence that it is not only muscle, but also fat loss that leads to these deleterious effects. The reasons why fat loss can be harmful in older persons are reviewed. There are four major causes of weight loss in older persons viz. anorexia, sarcopenia, cachexia and dehydration. This review concentrates on the major causes of anorexia and sarcopenia. In particular, the emergence of new medications such as selective androgen receptor molecules, antimyostatin analogues, megestrol acetate (nanocrystal formulation), and ghrelin agonists are reviewed. The potential role of anabolic steroids is also discussed.
Keywords: new medications